P26 How does the salford lung study in copd (sls copd) patient population fit into the gold 2017 classification grid?. (15th November 2017) - Vestbo, J; Boucot, I; Frith, L; Bakerly, N Diar; Collier, S; Leather, DA; Gibson, JM; Woodcock, A
Abstract : Background: GOLD 2017 separates spirometric staging from the 'ABCD' groupings defined by symptom burden/exacerbation risk. SLS COPD, a 12 month randomised controlled trial, demonstrated the effectiveness and safety of initiating fluticasone furoate/vilanterol versus continuing usual care in COPD patients in UK primary care (Vestbo J et al, New Engl J Med 2016;375:1253–60). Aim: Map SLS COPD patient distribution and treatment patterns to the GOLD 2017 classification grid. Methods: In this post-hoc analysis, patients were classified by GOLD 2017 (groups A–D based on exacerbation frequency history and baseline CAT score) and by the previous spirometry-based GOLD 2007 system (stages 1–4 based on baseline post-BD FEV1 ). Results: Baseline characteristics were (ITT; n=2799): 49%≥2 moderate/severe exacerbations in past year; 90% CAT score ≥10; 14% on long-acting BD only, 34% ICS ±LABA or LAMA, 52% ICS/LABA+LAMA. The figure shows key data. Distribution by GOLD 2017 was (n=2796): A 7%; B 43%; C 3%; D 47% and by GOLD 2007 (n=2199 with spirometry data): no airflow obstruction 12%; 1 10%; 2 48%; 3 24%; 4 5%. Around 60% of patients had mild/moderate airflow obstruction while 90% were GOLD group B/D due to symptoms and exacerbation risk. GOLD ABCD distribution and treatment patterns in patients without spirometry data were similar to the overall population. Conclusion: These data suggest that COPD exacerbations and symptoms are driving appropriate GP COPD management in routine primary care. Funding: GSK (HZC115151/NCT01551758 ). Please refer to page A258 for declarations of interest in relationto abstract P26.